SEED GERMINATIONS OF PESSEGUEIRO-BRAVO UNDER DIFFERENTS CONDITIONS OF LIGHT AND SUBSTRATUM - RODRIGUES, Elisangela Ronconi; HIRANO, Elcio; NOGUEIRA, Antonio Carlos (Scientia Agraria, 2008)
The objective of this work was to evaluate the influence of the light and substrata in the conduction of germination tests of Prunus sellowii Koehne. The tests had been carried through in the Laboratory of Forest Seeds of the Universidade Federal do Paraná (UFPR) and consisted of two experiments: the first one involved four conditions of light (white, red, red-extreme and absence of light) and as, four substratum (sand, vermiculite, agar and paper roll. The Speed Germination Index (IVG) and the percentage of germination had been evaluated. The seeds had presented greater germination under white light and in the absence of light, with 57% and 51% respectively. The IVG, under influence of the light conditions, did not differ between itself. How much to substrata, agar provided to minor germination that the paperroll, with 37% and 76% respectively. The too much substrata had not differed between itself. The IVG was minor to agar it in relation to the too much substrata, that had not shown differences between itself. One sends regards, therefore, for tests of germination of seeds of Prunus sellowii Koehne, the use of paper rolll, indifferently of the presence or not of white light.